Magnetocaloric properties of a novel ferromagnet Gd3Co4+xAl12−x (x = 0.50). (May 2015) - Pasturel, Mathieu; Nasri, Nabil; Gastebois, Justine; Guizouarn, Thierry; Belgacem, Besma; Ben Hassen, Rached; Tougait, Olivier
Abstract: A novel gadolinium and cobalt based aluminide, namely Gd3 Co4+x Al12−x (x = 0.50(3)) is shown to crystallize in the hexagonal Gd3 Ru4 Al12 structure-type (space-group P63 /mmc, a = 8.6830(1) Å, c = 9.3164(2) Å at room temperature). The investigation of its magnetic properties revealed a reversible ferromagnetic ordering at TC ≈ 40 K but expanding in a wide temperature range, potentially due to the geometrical magnetic frustrations expected in this structure-type. The magnetocaloric properties of this intermetallic, determined from both magnetization and specific heat data, are dominated by a maximum entropy variation of −3.28 J kg −1 K −1 at 39(1) K and an adiabatic temperature change of about 1.5 K extending from 20 to 40 K, highlighting some interest for low temperature applications. Highlights: Gd3 Co4.5 Al11.5 crystallizes with the hexagonal Gd3 Ru4 Al12 structure-type. The magnetic atoms are forming a distorted Kagomé lattice. It orders ferromagnetically in a quite extended temperature range below 40 K. It presents interesting features for low temperature magnetocaloric cooling.